POLITICAL ISSUES MANAGEMENT; CASE STUDY OF NEGATIVE ISSUES MANAGEMENT OF WEST JAVA PROVINCIAL GOVERNMENT IN 2019 - Wahyuni, Itca Istia; Atnan, Nur (JWP (Jurnal Wacana Politik), 2023)
The purpose of this study is to analyze how the Public Relations of the West Java Provincial Government manage the negative issues. The results of this study are used to provide recommendations for the political area to approach an accurate strategy, so the impact of negative issues can be less impacted and more controlled. The negative perspectives of the Institution will be impacted to Governor’s image as the highest leader. The methodology used in this study is a case study by selecting two controversial cases that caused a negative image of the West Java Provincial Government. The first issue that analyzes was the West Java Provincial Government Secretary corruption. The Second Issue was the Governor’s swimming pool which used a lot of Institutional budgets. The results of this study showed that the curative aspect is dominant in the management issues process. Furthermore, press conferences are the dominant strategy tool used by West Java Provincial Government Public Relations to inform how they solve any problem. The aspect that must be improved in neutralizing issues consists of the less in-depth trend analysis, and several media has not been classified properly.